Organizational identification among virtual workers: the role of need for affiliation and perceived work-based social support - Wiesenfeld, Batia M.; Raghuram, Sumita; Garud, Raghu (Journal of Management, 2001)
Organizational identification, which reflects how individuals define the self with respect to their organization, may be called into question in the context of virtual work. Virtual work increases employees’ isolation and independence, threatening to fragment the organization. This study finds that virtual workers’ need for affiliation and the work-based social support they experience are countervailing forces associated with stronger organizational identification. Furthermore, perceived work-based social support moderates the relationship between virtual workers’ need for affiliation and their strength of organizational identification. Thus, when work-based social support is high, even workers with lower need for affiliation may strongly identify with the organization.